Isolation and characterization of bacteria from the feathers of wild Dark-eyed Juncos (Junco hyemalis). (3rd February 2016) - Dille, John W.; Rogers, Christopher M.; Schneegurt, Mark A.
Abstract: We dislodged microbes from samples of composites of ventral feathers from different birds of overwintering Dark-eyed Juncos ( Junco hyemalis ) after mist-net capture in south-central Kansas, USA. Bacterial loads were measured by standard plate counts and >300 isolates were purified by repetitive streak-plating on R2A medium (+ cycloheximide). Biochemical and physiological characterization included identification by 16S rRNA gene phylogeny. Nearly half of the isolates grew on keratin and 80% exhibited lipase activity, suggesting that these isolates can degrade feathers and thus may affect survival and reproduction. Individual bacterial loads from 8 juncos varied within a 3-fold range, 10 5 –10 6 colony-forming units g −1 feather. At 97% DNA sequence identity (species-level), 63 operational taxonomic units were detected among 202 sequences; the Chao1 estimate was 123. The Shannon diversity index ( H ; 97% identity) was 3.75, Simpson's diversity index (1/ D ) was 16.1, and Good's coverage was 82.4. Gram-positive bacteria dominated the culture collection, balanced between low and high G+C clades. Bacillus spp. were abundant, including B. asahii, B. cereus, B. megaterium, and B. pumilus . Lysinibacillus, Paenibacillus, and Staphylococcus also were isolated. Remarkably, substantial numbers of Actinomycetes were isolated, including representatives of Clavibacter, Curtobacterium, Microbacterium, and Rathayibacter, genera recognized as being populated by xylem-filling crop plant pathogens. Apposed to these were feather isolates implicated as beneficial to host plants, Frigoribacterium and Kitasatospora, being antagonists to plant pathogens or acting as plant growth promoters. High G+C Gram-positive bacterial isolates included Blastococcus, Cellulomonas, Humicoccus, Nocardioides, Promicromonospora, and Rhodococcus. Proteobacteria dominated the Gram-negative bacteria, with Alphaproteobacteria most abundant, including the potential plant pathogens Agrobacterium and Sphingomonas, and the oligotrophs Aurantimonas, Brevundimonas, Methylobacterium, Rhizobium, and Rhodobacter. Gammaproteobacteria included Pantoea, Pseudomonas, and Stenotrophomonas . Ours is the first report of abundant helpful and harmful phyllosphere bacteria on wild bird feathers. The clear implication is that free-living migratory birds may carry bacteria throughout their geographic ranges and may transmit pathogens and beneficial bacteria to plants.